Liver-targeted transcription activator-like effector repressors that inactivate HBV cccDNA - Kaldine, Haajira (My University, 2017)
The hepatitis B virus (HBV) continues to be a global health threat as chronic infection may lead to cirrhosis and hepatocellular carcinoma (HCC). Current treatments are limited in efficacy and do not target the stable HBV covalently closed circular DNA (cccDNA) minichromosome which forms the template for viral replication and is responsible for persistence of the infection. Using gene editing technologies to disable cccDNA presents a potential approach for treating HBV infection. Transcription activator-like effector (TALE) proteins provide specific and adaptable DNA binding modules, which can be used to generate engineered proteins capable of modifying DNA. Transcription activator-like effector nuclease (TALEN) mediated cleavage of cccDNA has been shown to effectively inhibit HBV replication. However, the approach to transcriptionally silence cccDNA, instead of cleaving it, may overcome the risk of unwanted host DNA cleavage. Repressor transcription activator-like effectors (rTALEs), which target and transcriptionally silence genes, have shown potential as antiviral agents. Here we generated Krüppel-associated box (KRAB)-based rTALEs targeted to the surface open reading frame (ORF) and HBx promoter region of HBV cccDNA to inhibit transcription. The rTALEs were placed under the transcriptional control of the liver-specific modified murine transthyretin (mTTR) promoter, to restrict activity to hepatocytes thereby reducing the potential for off-target activity. In vitro the mTTR-driven rTALEs were shown to tissue specifically decrease secreted HBV surface antigen (HBsAg) levels by 63 - 92 %. Additionally, the mTTR-driven rTALEs were shown to tissue specifically decrease surface mRNA levels by 65 – 81 % and pregenomic RNA levels by 60 - 76 %. These results indicate that the KRAB domain was able to effectively suppress transcription from the basic core, Pre-S1 and/or vi Pre-S2 promoters which otherwise regulates HBV transcription. Furthermore, the observed inhibition was not associated with cytotoxicity or off-target effects. The work presented here is a proof-of-concept study demonstrating that highly specific transcriptional repressors designed to target and inhibit HBV viral replication without altering the genetic sequence or causing mutations in the host genome may be a promising antiviral approach. The capabilities of this technology to directly target cccDNA and inhibit its transcription, could contribute to addressing a global health problem.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science in Medicine Johannesburg, 2017.
Keywords: Hepatitis B virus; Transcription Activator-Like Effector Nucleases; Carcinoma, Hepatocellular; DNA, Circular